The effect of pro-entrepreneurship architecture on organisational outcomes - Urban, Boris (Journal of Business Economics and Management, 2012)
Recent years have seen considerable work at the interface between business, management, entrepreneurship and strategy and as a result, new research domains have appeared including corporate entrepreneurship and entrepreneurial strategy. The purpose of this article is to understand the effect that corporate entrepreneurship strategy has on firms to revitalize, reconfigure resources and transform into firms that are ready to compete in the global economy. Empirical tests are conducted to determine to what extent elements of pro-entrepreneurship architecture are able to predict development capability, strategic repositioning, and growth based outcomes. A first-phase survey is conducted to verify the presence and strength of entrepreneurial orientation while the second phase of the study identifies elements of organizational architecture able to predict firm outcomes. The main contribution of this article is that firms resourcing and rewarding policies, as well as cultural and structural orientations, derived from a corporate entrepreneurship strategy, play a significant role in realizing desired outcomes. The study has important implications for emerging economies where growth is often the primary goal of organizations, and where corporate entrepreneurship can be critical for firm profitability and survival.